The Supply at Saint Agatha's - Phelps, Elizabeth Stuart, 1844-1911; Smith, E. Boyd (Elmer Boyd), 1860-1943; Woodbury, Marcia Oakes, 1865-1913 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Supply at Saint Agatha's" by Elizabeth Stuart Phelps is a novel written in the late 19th century. Set in a fashionable church in a nameless city, the book explores themes of faith, sacrifice, and the moral responsibilities of a community towards its less fortunate members. Through its central narrative, it addresses the duties of a pastor and the impact of genuine compassion on the human spirit. The story revolves around an old clergyman, who, despite battling health issues, responds to a call to serve at the prestigious Saint Agatha's Church. However, a stormy night and his subsequent illness prevent him from fulfilling this promise. Instead, a mysterious and charismatic substitute preacher arrives, captivating the audience with a powerful message that transcends social classes and addresses the sins and struggles of humanity. This preacher encourages the congregation to seek out and support the marginalized, ultimately leaving a lasting impact that resounds within the church and its attendees. The narrative culminates in the profound realization of faith and connection amid societal privilege, highlighting the essential call to service and love that lies at the heart of Christianity. (This is an automatically generated summary.)
Release date is 2010-11-08
Produced by Al Haines
Keywords: Short stories; Clergy -- Fiction; Churches -- Fiction